Common Purpose: Performance and Curation as Allied Socially Engaged Practices. Issue 1 (1st March 2022) - Bunt, Brogan
Abstract: The relationship between performance and curation has shifted. A new attitude of fluid and pragmatic alliance has evolved as the sense of an essential antagonism between performance and curation recedes and the two fields discover a shared focus on aspects of social engagement and agency. This article considers an Australian socially engaged art project, the Kandos School of Cultural Adaptation (KSCA), which meshes curatorial and artistic practices in its efforts to reimagine and reanimate the future of a small country town. Employing a wide range of strategies, KSCA works closely with the local community to facilitate collective memory, reflection and social and environmental transformation. Deliberately avoiding traditional lines of artistic and institutional tension, KSCA employs an impure and inclusive approach that is emblematic of emerging forms of activist contemporary art.